Heart work : the handbook on the surviving and thriving of cultural and identity centers in higher education - Felix, Alex Romero; Mendoza, Gary Santos; Torres-Baez, Daisy; Davis, Lori Patton (Emerald Publishing Limited, 2025)
Heart Work: The Handbook on the Survival and Success of Cultural and Identity Centers in Higher Education highlights the experiences of higher education professionals working in these centers. This handbook offers a blend of personal stories and the latest research on cultural and identity centers, building on Dr. Lori Patton Davis' 2010 book, Culture Centers in Higher Education: Perspectives on Identity, Theory, and Practice. Since 2010, these centers have navigated significant challenges, including the global COVID-19 pandemic, and have increased focus on institutional racism. The book delves into the experiences and histories of various cultural and identity centers, including Latinx/e Cultural Centers, Asian, Pacific Islander, Middle Eastern Arab and Desi Cultural Centers, Native American/Indigenous Cultural Centers, Black/African American Cultural Centers, Disability Cultural Centers, Lesbian, Gay, Bisexual, Transgender, Queer+ Centers, and Undocumented Student Resource Centers. In light of recent events affecting minoritized populations, it also covers topics such as evolving practices in cultural/identity centers, university politics, and strategies for practitioners to advance and sustain the Heart Work. Heart Work offers community members - especially practitioners, faculty, and staff in higher education - an understanding of the recent environmental context of cultural and identity centers. As our society evolves, recognizing that identities are not monolithic and embracing intersectionality allows for a deeper understanding of oppression and lived experiences. This handbook aims to bridge the gap by continuing the research and practice of cultural and identity centers in higher education.
Includes index.
Keywords: Inclusive education.; Minorities in higher education.; Education -- Inclusive Education.; Educational strategies and policy: inclusion.; elektronické knihy; electronic books